Optimalizace organizační struktury - Marquardt, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Cílem této diplomové práce „Optimalizace organizační struktury“ je analýza organizačního uspořádání společnosti Bosch Rexroth, s. r. o. zaměřená na soulad organizační struktury s firemními procesy a strategickým zaměřením a návrh nové optimální organizační struktury na základě literární analýzy zásad pro vytváření optimálních organizačních struktur.

The aim of this diploma thesis “Optimalization of organization structure” is the analysis of the current organization form of the company Bosch Rexroth, s r.o. focused on conformity with the organisation processes and the strategic plans and to propose the new optimal organisation. based on the literary analysis of conventions for creating of optimal organisation structures.
Optimalization of Organization Structure
Keywords: Organizační struktura; optimalizace; strategie; procesy; organization structure; optimalization; strategy; proceses